Effect of Bavistin and Silver Thiosulphate on In Vitro Plant Regeneration of Stevia rebaudiana - C.V. Naidu, D. Preethi1, T.M.Sridhar1 and (Journal of Phytology, 2011)
Effect of Bavastin (fungicide), Silver thiosulphate (Ehtylene inhibitor) on shoot regeneration using axillary bud explants of Stevia rebaudiana was studied. In Bavastin supplemented medium multiple shoots were induced from axillary bud explants. Bavistin in combination with BA induced maximum number of shoots (6.4±0.2). Ethylene inhibitor silver thiosulphate also favoured the shoot morphogenesis. At lower concentration of silver thiosulphate (10-40 mM/L) maximum number of shoots (2.1-3.2) were obtained. All the in vitro raised shoots with a length of 3-5 cm were transferred to rooting medium. The best rooting response was observed on 2.0mg/L IBA. The well rooted plantlets were transferred to polybags containing soil + vermiculite in 1: 1 ratio for hardening. Finally the hardened plantlets were transferred to field conditions for maximum survivability.